Navigating climate change impacts on agricultural productivity, food and human health security in developing countries - Fatima Azdagaz; Omar Zirari; Mariem Liouaeddine (Global Transitions)
This study examines climate change impacts on agricultural productivity and human health across 20 developing countries (2000–2020) using Panel Autoregressive Distributed Lag (Panel-ARDL) methodology. Our systems approach models dynamic relationships between climate variables, food production, and nutritional outcomes, addressing multicollinearity through variance inflation tests and alternative specifications. National carbon dioxide (CO2) emissions serve as proxies for multiple climate pathways including temperature variations and economic development patterns affecting food systems. Results reveal strong negative long-run relationships between CO2 emissions and food production, with positive associations with child stunting. The Pooled Mean Group estimator demonstrates homogeneous long-run coefficients while allowing heterogeneous short-term dynamics across countries. The paradoxical positive CO2-food insecurity relationship reflects greater climate stresses and inequitable benefit distribution in higher-emission countries. Health impacts exhibit greater persistence than production shocks, emphasizing comprehensive monitoring needs. Findings suggest integrated policies combining climate mitigation, productivity enhancement, and health system strengthening for resilient food systems.